ANALISIS KEPUASAN PENGUNJUNG DENGAN IMPORTANCE PERFORMANCE ANALYSIS DI WISATA PANTAI TOPEJAWA KABUPATEN TAKALAR PADA ERA KENORMALAN - Nuzmiyah Shaleh; Rusmin Nuryadin; Nur Ifra Khumaera (Jurnal Ekonomi Integra, 2022)
One of the tourism objects that is developing in South Sulawesi is Topejawa Beach, which is located in Takalar Regency. Topejawa Beach is one of the favorite and leading tourist attractions in Takalar Regency. With the availability of adequate facilities and infrastructure for tourists, it becomes one of the attractions for tourists to come to visit. Therefore, in the development of Tojawa Beach tourism, it is necessary to organize it effectively and efficiently in order to get a positive perception from tourists. The purpose of this study was to analyze the level of satisfaction of visitors to the Topejawa Beach tourist attraction. The method in this study is the Important Performance Analysis (IPA) method to determine the level of customer satisfaction. Based on the results of the IPA analysis of five variables, namely the image of a tourist attraction, cost, attractions, accessibility, and facilities and services, it is found that the important factor to be addressed (quadrant I) is the image of a tourist attraction. Furthermore, the factors that are considered to have satisfied visitors (quadrant II) are costs and attractions. The factor that is considered not urgent by visitors (quadrant III) is accessibility and the last factor that is considered less important or given too much is the facilities and services in Topejawaa tourism.